1990
DOI: 10.1246/cl.1990.251
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Highly Selective Reduction of Tertiary Amides to Amines with Sodium Borohydride-Bis(2-bromoethyl)selenium Dibromide

Abstract: Treatment of tertiary amides with sodium borohydride-bis(2-bromoethyl)selenium dibromide in THF gave the corresponding amines, although the similar reactions of secondary and primary amides could not proceeded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The reduction of the amide bond by complex metal hydrides has significant synthetic importance for obtaining various amines. Some amide compounds are able to react with amines, known as an acyl transfer or transamidation reaction (Scheme ). These processes represent very efficient transformations in synthetic organic chemistry towards selectively obtaining various amide structures from amino compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of the amide bond by complex metal hydrides has significant synthetic importance for obtaining various amines. Some amide compounds are able to react with amines, known as an acyl transfer or transamidation reaction (Scheme ). These processes represent very efficient transformations in synthetic organic chemistry towards selectively obtaining various amide structures from amino compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the structures of 4, 5 and 6, the four carbon atoms (the 1,2, I', 2' positions of the cyclohexane rings) which bond to the selenium or oxygen atoms of the aikoxy groups (7) may be asymmetric carbon atoms. However, the addition of selenium and alkoxy groups to the carbon-carbon double bond proceeded stereospecifically to give anti-addition products as described below.…”
mentioning
confidence: 99%
“…In 1990 Akabori and co‐authors reported a tertiary amide reduction with NaBH 4 in combination with bis(2‐bromoethyl)selenium dibromide. [ 198 ] This protocol can be applied only to the tertiary amides, while secondary and primary amides remain intact under these conditions. Following the procedure, Et 3 N was prepared in 70 % yield using 5 equivalents of NaBH 4 .…”
Section: Trialkylamines Synthesismentioning
confidence: 99%